Athletes’ Psychological Adaptation to Confinement Due to COVID-19: A Longitudinal Study - Rubio, Víctor J.; Sánchez-Iglesias, Iván; Bueno, Marta; Martin, Gema (Frontiers in Psychology, 2021)
Studies of individuals under conditions of confinement or severe social and physical restrictions have consistently shown deleterious mental health effects but also high levels of adaptability when dealing to such conditions. Considering the role of physical activity and sport in psychological adaptation, this paper describes a longitudinal study to explore to what extent the imposed restrictions due to the outbreak of SARS-CoV-2 may have affected athletes’ mental health outcomes and how far the process of adaptation to confinement conditions is differentially affected depending on whether the sports activity was practiced individually or in a group, and outdoors, indoors or both. Two hundred and seventy-four athletes were assessed over 7 weeks using the GHQ-28 and an ad hoc survey exploring the practice of physical activity. A mixed-model fixed effects ANCOVA was used to analyze the effects of time, place and company in which the sport was practiced, with an index of the amount of physical activity expended as a covariate. Results show a significant effect of time in three out of four of the GHQ-28 subscales, in all cases showing a consistent adaptation to conditions over time. Results also show that playing sport indoors, outdoors or both, and practicing alone vs. with others, differentially affect the somatic symptoms exhibited during confinement: Athletes who practiced sport with others showed higher levels of somatic symptoms at the beginning of the set of data but quicker rate of adaptation. Differences arising from practicing sport alone or with others were more pronounced in the case of indoor sports, which could be related to the fact that physical activity that can be practiced during confinement is more similar to that practiced indoors alone. Implications relating to what sport psychologists and other health professionals may offer to athletes in stressful situations are discussed.